The Effectiveness of a training program to reduce stuttering intensity among primary school students in Ajloun schools - Al- qwaqneh, Bara Azzam Ali (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal the effectiveness of a training program to reduce stuttering disorders in primary school students in Ajloun schools in Jordan. Five dimensions of stuttering disorders were identified. Third grade students in Ajloun Elementary Boys School were distributed equally to experimental and control group. Ij study, there is statistically significant in all disorders of the dimensions of stuttering in the third grade primary students are differences in the two measurements prior and subsequent to the performance of the control and experimental groups students due to the training program used in the study, for the experimental group, which underwent a program to reduce the severity of stuttering students.
Keywords: Training program; stuttering disorders; basic stage students